Mechanism and kinetics of gold leaching from copper anode slime using BmimHSO4 as green solvent. Issue 5 (20th January 2022) - Hernashki, Roya Kafi; Rezvani, Ali Reza; Khayati, Gholam Reza; Saheli, Sania
Abstract: The cyanide process, as the most common approach in the recovery of gold by hydrometallurgical, suffers from its high toxicity to the environment. The effect of practical parameters, viz., temperature, time, concentration, mechanical activation, and the stirring rate, was investigated using a combination of H2 O2, BmimHSO4, and thiourea as green solvent to recover the gold from anode copper slime in an electrorefining plant. The leaching kinetics of Au in the selected slime was also investigated. The results showed that leaching reaches 93.48% after 20 h in the activated sample for 10 h at the temperature of 313.15 K and solvent including 60% (v/v) BmimHSO4, 50 g/L thiourea, 1/15 g/ml pulp density, 25 g/L H2 O2, and an agitation speed of 400 rpm. Moreover, the leaching of Au follows the shrinkage particle model, and the diffusion of a solvent through the leaching product was the administrated mechanism. The proposed green solvent can also dissolve gold effectively and is an excellent candidate to replace harmful cyanide‐based solvents.